Implementing and Designing Interactive Governance Arenas: A Top-Down Governance Perspective - Hagedorn Krogh, Andreas (Scandinavian Journal of Public Administration, 2017)
Mandating interactive governance arenas presents itself as an appealing strategy for deter- mined public policy-makers at the frontier of New Public Governance. However, it also confronts researchers and practitioners with a new set of policy execution problems which prompts re-examination of one of the oldest research questions in public administration research: how and why are the high hopes of central policy-makers (not) translated into practice? Through combining insights from the public policy implementation literature, network governance literature and theories of multi-actor institutional design, the article develops a theoretical perspective for studying top-down implementation of interactive governance arenas. The developed perspective enables researchers and practitioners to identify a number of critical junctions in the implementation process with important impli- cations for the final design of the interactive arenas. A longitudinal case-analysis of the implementation of ten Local Crime Prevention Councils in one of twelve Danish police districts is conducted to demonstrate how the perspective may be deployed in empirical studies.